Religious Moderation in Multicultural Education Management Practices: Elementary School Strategies in Facing Diversity Challenges - Ahmad, Munir (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2024)
The main issue addressed in this study is the weak internalization of religious moderation values in primary education institutions when dealing with diversity. A lack of understanding of differences and the limited implementation of multicultural education may lead to intolerance. Therefore, it is important to examine how multicultural education management practices in elementary schools can serve as effective strategies for instilling moderate values and shaping tolerant and inclusive generations. This study employs a descriptive qualitative approach with field research conducted at SD Pelita Hati Jember. Data were collected through participant observation, semi-structured interviews, and documentation using purposive sampling. Data analysis followed the Miles, Huberman, and Saldaña model, which includes data condensation, display, and verification. Data validity was ensured through triangulation and member checking. The findings indicate that SD Pelita Hati Jember demonstrates a strong commitment to inclusive and globally oriented multicultural education through the integration of the 2013 National Curriculum and the Cambridge curriculum, tolerant leadership, and cross-cultural programs. Active learning and inclusive teaching practices help shape students’ religious moderation. However, infrastructure limitations remain a key challenge. Sustaining multicultural education requires institutional support and enhanced teacher capacity. This school serves as a strategic model for building moderate character in Indonesia’s plural society. This study contributes by providing an applicable model of multicultural education management in elementary schools. The findings offer valuable insights for policymakers and educators in designing inclusive learning strategies to promote moderate character in the context of Indonesia's diverse society.